Investigating women’s agency and achievements in agriculture: Insights from APART, Assam - Varkey, Lisa Mariam; Veettil, Prakashan Chellattan; Singh, Kanwar; Borgohain, Rupam; Bhattachrya, Ashok; Singh, Sudhanshu (International Rice Research Institute, 2023)
Women play an important role in agriculture and account for around 50% of the agricultural labor force in Asia. Strong evidence exists to prove that women farmers have less access to land, inputs, labor and information compared to men, which, in turn, can influence technical efficiency in farms, that is the effectiveness with which a given set of inputs is used to produce output. Strong reasons indicate that women’s empowerment may contribute to enhancing technical efficiency, most notably through improvements in women’s access to human, physical, and social capital. In this study, using plot-level data from the 2022 impact evaluation study under Agribusiness and Rural Transformation Project (APART), we first measure women’s empowerment under six dimensions for the beneficiary women farmers using Abbreviated Women’s Empowerment in Agriculture Index. Thereafter, we proceed to estimate a stochastic frontier production function model, which includes women’s empowerment in agriculture as an exogenous determinant of technical inefficiency. We find that the women-operated paddy plots in our study exhibit 66 % efficiency whose productivity is significantly influenced by all labor and material inputs. Our study also finds women empowerment as a strong predictor of technical efficiency. With lower technical efficiency reported in plots owned by the households where women hold unequal rights, our results also subtly point to the occurrence and impact of hidden gender disparities within a household, existing in the form of land titles. Our study supports the idea why women empowerment should be pursued for its intrinsic value as a developmental goal in itself and instrumental value for furthering other developmental outcomes.